(untitled) (Nepal Medical College Journal, 2020)
Community-acquired pneumonia (CAP) remains a common and serious illness, in spite of the availability of potent new antimicrobials and effective vaccines. Despite Nepal being one of the four developing countries accounting for 40.0% of global acute respiratory infections, studies on CAP are limited and the status of adult pneumonia in our community is unknown. This cross-sectional study reviewed the clinical, bacteriological, radiological profile of 100 cases of adult CAP and followed them during the hospital stay for the outcome. The age group with the highest incidence was 60-79 years with females (55.0%) being more affected than males (45.0%). Risk factors were present in 86.0% of cases, chronic obstructive pulmonary disease (COPD), and smoking was the most common, each present in 43.0% of cases. The most common presenting feature was cough (89.80%) followed by sputum production (78.60%), fever (67.30%), shortness of breath (63.30%), chest pain (38.80%), gastrointestinal symptoms (26.50%), altered sensorium (13.30%), and hemoptysis (13.30%). Only 48.0% of patients had leukocytosis. Klebsiella pneumoniae was the most frequent organism isolated (n=4) followed by Pseudomonas aeruginosa (n=3). Fungi were isolated in 3 cases. Lobar pneumonia was seen in 99.0% of cases with the right lower zone being the most commonly involved zone on chest x-ray. Severe pneumonia with CURB-65 (confusion, blood urea nitrogen, respiratory rate, blood pressure, age>65) Score ≥3 was seen in 15.0% of cases. The mean hospital stay was 7.55 days with 28 cases requiring ICU admission and 5 cases of mortality.